Volatilitas harga daging dan telur ayam ras di Indonesia - Mubarok, Atikah Fajriyah; Setiadi, Agus; Komalawati; Wulandari, Suci; Yusuf, Eddy Supriadi (Analisis Kebijakan Pertanian, 2024)
Chicken meat and eggs are important food commodities for national food security and nutrition. The volatility of chicken meat and egg prices can potentially affect food inflation increase and chicken farmer income. This study analyzes the volatility of chicken meat and egg prices and the factors influencing them. The data used are daily chicken meat and egg prices from July 2017 to October 2022. Price volatility analysis using the ARCH/GARCH model and the factors that influence it are examined through price volatility graphs. The results of the study estimate that the price of chicken meat has a volatility coefficient of 0.281, indicating low volatility that does not last long due to the absence of the GARCH coefficient. Meanwhile, the price of chicken eggs has a volatility coefficient of 0.028 and a persistence of 0.961, indicating low but persistent volatility in the long term. Factors that influence the volatility of chicken meat and egg prices include oversupply, farmer decisions regarding the productive period of chickens, production and distribution constraints due to the rainy season, increases in feed and DOC prices, high demand on festivity days, and supply chain disruptions during the COVID-19 pandemic. The analysis shows that efforts to improve coordination to prevent excess supply, strengthen production scheduling, and provide incentives for farmers are needed to maintain the stability of chicken meat and egg prices.